Degradable environment-friendly plastic film and preparation method thereof
By combining modified SiO2 particles with starch, the existing degradable plastic films have been solved in water absorption and microbial erosion, extending their service life and reducing light transmittance, forming an efficient degradable and environmentally friendly plastic film.
Patent Information
- Application Number
- CN202411559572.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The existing biodegradable plastic films have problems in water absorption and microbial erosion, resulting in a decrease in strength and shortened service life, while their light transmittance is high, affecting their application.
Modified SiO2 particles are combined with starch. The modified SiO2 particles have a hydrophobic and incompletely closed cavity structure. The starch is stored inside it to avoid water absorption and microbial erosion, and reduce light scattering by adjusting the particle size, forming a degradable degradation. Environmentally friendly plastic film.
It improves the hydrophobicity of the film, extends the service life, reduces the light transmittance, and enhances strength and stability.
Smart Images

Figure CN119264590A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and in particular relates to a degradable environmentally friendly plastic film and a preparation method thereof. Background Art
[0002] At present, various plastic films, such as PET film, PMMA film, PE film, etc., have been widely used in chemical, medical, pesticide and food fields. Among them, packaging films made of these plastic films account for the largest proportion. However, since most of these plastic films are non-degradable, they pose a great threat to the ecological environment and may even endanger human health or animal life. This is because the covalent bonds on the main chain of the polymer in the plastic are very strong, and it is difficult to degrade naturally when entering the environment. Burning is the most convenient way to deal with plastic pollution, but the waste gas generated by burning polymers will pollute the environment. Therefore, the development of degradable plastic films is of great significance.
[0003] At present, most degradable plastic films are made by mixing synthetic high molecular polymers with natural polymers. This type of film has achieved good results in terms of degradability. However, the addition of natural polymers such as starch, cellulose and other materials will cause some negative problems. For example: 1. Starch contains a large number of hydroxyl groups, which easily absorbs water molecules, causing the film structure to be destroyed, which may soften the plastic film and reduce its strength; 2. Starch is a polysaccharide that is easily eroded by microorganisms, which affects the life of the film; 3. When starch and high molecular polymers are mixed, uneven dispersion may affect the quality of the film and light transmittance. Summary of the invention
[0004] The present invention provides a degradable environmentally friendly plastic film and a preparation method thereof to overcome the drawbacks of the prior art. The film is hydrophobic, and can avoid the problem that starch molecules absorb water, causing the plastic film to become soft and the strength to decrease. It can slow down the erosion of starch by microorganisms, increase the service life of the film, reduce the scattering of light, and reduce the impact on the light transmittance of the film.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] A degradable and environmentally friendly plastic film is provided, the raw materials of the plastic film are made of the following materials:
[0007] Polyacrylic acid: 40-60 parts by mass;
[0008] Starch: 20-30 parts by weight;
[0009] Modified SiO2 particles: 10-15 parts by mass;
[0010] Benzoyl peroxide: 2-4 parts by weight;
[0011] Silane coupling agent KH-570: 3 to 6 parts by mass;
[0012] Polyethylene glycol: 2 to 4 parts by weight;
[0013] The modified SiO2 particles have an incompletely closed cavity structure, the starch is inside the cavity of the modified SiO2 particles, the hydroxyl (-OH) groups on the surface of the modified SiO2 particles in the solution are replaced by alkyl (-CH3) groups, and the diameter of the modified SiO2 particles is 30 to 150 nm.
[0014] Combine starch with modified SiO2 particles. The surface of modified SiO2 particles is -CH3 (methane) instead of -OH (hydroxyl), making it hydrophobic, thus avoiding the problem of starch molecules absorbing water and causing the plastic film to soften and lose strength. In addition, starch can be carried inside the cavity of modified SiO2 particles, slowing down its erosion by microorganisms and increasing the service life of the film. The particle size of modified SiO2 particles is small, about 30 to 150nm. After carrying starch, it is easy to composite with high molecular polymers. The size is 30 to 150nm, and the light scattering effect will be greatly reduced, which can reduce the impact on the transmittance of the original film.
[0015] As a further preferred degradable environmentally friendly plastic film.
[0016] Preferably, the preparation of modified SiO2 particles comprises the following steps:
[0017] S11, dissolving 0.3 parts by mass of polyacrylic acid in 6-8 parts by mass of ammonia water, stirring for 1 hour, then adding 50-80 parts by mass of anhydrous ethanol, stirring for 2 hours, and finally adding 0.5-1 parts by mass of tetraethyl orthosilicate, continuing to stir and react for 5-10 hours, and finally washing with deionized water to obtain open-pored SiO2 particles;
[0018] S12. Add 100 parts by mass of anhydrous ethanol to 4 parts by mass of open-pored SiO2 particles, then add 1 to 2 parts by mass of hexamethyldiazapine and stir for 3 to 6 hours, and then centrifuge to obtain modified SiO2 particles.
[0019] During the synthesis, it is critical to control the amount of ammonia. When the amount of ammonia is small, the micelles formed by polyacrylic acid are too large. As the SiO2 template for forming the cavity structure, the micelles are too large in size, which will cause the size of the open-pore SiO2 particles to be too large. In addition, ammonia acts as a catalyst in the reaction of silicon source forming SiO2. When the amount is small, the reaction is slow and closed-pore hollow SiO2 particles will be formed, which will prevent starch from combining with external polyester. When the amount of ammonia is too much, the reaction of silicon source forming SiO2 will be very fast, resulting in its inability to grow on the micelle template and directly forming solid SiO2 particles.
[0020] The modified SiO2 particles have a large number of hydroxyl groups (-OH) in the solution and are hydrophilic. Through the modification of hexamethyldiazaalkane, the hydroxyl groups are replaced by alkyl groups, making them hydrophobic.
[0021] Preferably, the method for preparing starch inside the cavity of modified SiO2 particles comprises the following steps:
[0022] Add 6-9 parts by mass of starch to 50-80 parts by mass of deionized water, heat to dissolve, then add 3-4.5 parts by mass of modified SiO2 particles, stir for 10 minutes, then lower the temperature, let stand to precipitate, immediately centrifuge to obtain white powder, and then wash the white powder with cold water and ethanol.
[0023] After heating, the starch dissolves and enters the cavity of the modified SiO2 particles, and after cooling, the starch precipitates. By centrifugation, a mixture of modified SiO2 particles and starch can be obtained, and then the outer layer of starch is washed off with water to obtain the starch inside the cavity of the modified SiO2 particles.
[0024] The present invention also provides a method for preparing a degradable environmentally friendly plastic film, which comprises the following steps:
[0025] S21, feeding the raw materials described in claim 1 into an internal mixer and stirring them evenly, and then extruding the substrate melt;
[0026] S22, forming a degradable and environmentally friendly plastic film on a cooling roller with the melt in step S21.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) Compared with the original starch-based biodegradable film, this film is hydrophobic, which can avoid the problem of starch molecules absorbing water, causing the plastic film to become soft and the strength to decrease.
[0029] (2) Most of the starch is inside the cavity of the modified SiO2 particles, which can slow down the erosion of starch by microorganisms and increase the service life of the film.
[0030] (3) After starch and modified SiO2 particles are combined, their size is fixed at 30-150 nm, which can reduce the aggregation and the generation of oversized particles, reduce the scattering of light, and reduce the impact on the light transmittance of the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 (a)-1(b) are transmission electron micrographs and scanning electron micrographs of the modified SiO2 particles prepared in Example 1, respectively;
[0032] Figure 2(a)-2(b) are transmission electron micrographs of SiO2 particles prepared in Comparative Example 1 and Comparative Example 2, respectively;
[0033] Figure 3 is a photo of the degradable and environmentally friendly plastic film of Example 2;
[0034] Figure 4 are photos of plastic films prepared in Comparative Examples 3 and 4;
[0035] Figure 5 3 is the light transmittance curve of the plastic film prepared in Example 3, Comparative Example 3 and Comparative Example 4;
[0036] Figure 6 This is a scanning electron microscope photograph of the degradation of the degradable and environmentally friendly plastic film prepared in Example 3. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with embodiments and comparative examples.
[0038] Example 1
[0039] This embodiment provides a degradable and environmentally friendly plastic film and a preparation method thereof.
[0040] Preparation of modified SiO2 particles:
[0041] S11, dissolving 0.3 parts by mass of polyacrylic acid in 6 parts by mass of ammonia water, stirring for 1 hour, then adding 50 parts by mass of anhydrous ethanol, stirring for 2 hours, and finally adding 0.5 parts by mass of tetraethyl orthosilicate, continuing to stir and react for 5 hours, and finally washing with deionized water to obtain open-pored SiO2 particles;
[0042] S12. Add 100 parts by mass of anhydrous ethanol to 4 parts by mass of open-pored SiO2 particles, then add 1 part by mass of hexamethyldiazaethane and stir for 3 hours, then centrifuge to obtain modified SiO2 particles.
[0043] Preparation method of starch inside the cavity of modified SiO2 particles:
[0044] Add 6 parts by mass of starch to 50 parts by mass of deionized water, heat to dissolve, then add 3 parts by mass of modified SiO2 particles, stir for 10 minutes, then lower the temperature, let stand to allow precipitation to occur, immediately centrifuge to obtain white powder, and then wash the white powder with cold water and ethanol.
[0045] Preparation method of degradable environmentally friendly plastic film:
[0046] S21, 40 parts by mass of polyacrylic acid, 20 parts by mass of starch, 10 parts by mass of modified SiO2 particles, 2 parts by mass of benzoyl peroxide, 3 parts by mass of silane coupling agent KH-570 and 2 parts by mass of polyethylene glycol are fed into an internal mixer and stirred evenly, and then the substrate melt is extruded;
[0047] S22, forming a degradable and environmentally friendly plastic film on a cooling roller with the melt in step S21.
[0048] Example 2
[0049] This embodiment provides a degradable and environmentally friendly plastic film and a preparation method thereof.
[0050] Preparation of modified SiO2 particles:
[0051] S11, dissolving 0.3 parts by mass of polyacrylic acid in 7 parts by mass of ammonia water, stirring for 1 hour, then adding 60 parts by mass of anhydrous ethanol, stirring for 2 hours, and finally adding 0.7 parts by mass of tetraethyl orthosilicate, continuing to stir and react for 8 hours, and finally washing with deionized water to obtain open-pored SiO2 particles;
[0052] S12. Add 100 parts by mass of anhydrous ethanol to 4 parts by mass of open-pored SiO2 particles, then add 1.5 parts by mass of hexamethyldiazapine and stir for 4 hours, then centrifuge to obtain modified SiO2 particles.
[0053] Preparation method of starch inside the cavity of modified SiO2 particles:
[0054] Add 8 parts by mass of starch to 60 parts by mass of deionized water, heat to dissolve, then add 4 parts by mass of modified SiO2 particles, stir for 10 minutes, then lower the temperature, let stand to precipitate, immediately centrifuge to obtain white powder, and then wash the white powder with cold water and ethanol.
[0055] Preparation method of degradable environmentally friendly plastic film:
[0056] S21, 50 parts by mass of polyacrylic acid, 15 parts by mass of starch, 12 parts by mass of modified SiO2 particles, 3 parts by mass of benzoyl peroxide, 4 parts by mass of silane coupling agent KH-570 and 3 parts by mass of polyethylene glycol raw materials are fed into an internal mixer and stirred evenly, and then the substrate melt is extruded;
[0057] S22, forming a degradable and environmentally friendly plastic film on a cooling roller with the melt in step S21.
[0058] Example 3
[0059] This embodiment provides a degradable and environmentally friendly plastic film and a preparation method thereof.
[0060] Preparation of modified SiO2 particles:
[0061] S11, dissolving 0.3 parts by mass of polyacrylic acid in 8 parts by mass of ammonia water, stirring for 1 hour, then adding 80 parts by mass of anhydrous ethanol, stirring for 2 hours, and finally adding 1 part by mass of tetraethyl orthosilicate, continuing to stir and react for 10 hours, and finally washing with deionized water to obtain open-pored SiO2 particles;
[0062] S12. Add 100 parts by mass of anhydrous ethanol to 4 parts by mass of open-pored SiO2 particles, then add 2 parts by mass of hexamethyldiazapine and stir for 6 hours, and then centrifuge to obtain modified SiO2 particles.
[0063] Preparation method of starch inside the cavity of modified SiO2 particles:
[0064] Add 9 parts by mass of starch to 80 parts by mass of deionized water, heat to dissolve, then add 4.5 parts by mass of modified SiO2 particles, stir for 10 minutes, then lower the temperature, let stand to allow precipitation to occur, immediately centrifuge to obtain a white powder, and then wash the white powder with cold water and ethanol.
[0065] Preparation method of degradable environmentally friendly plastic film:
[0066] S21, 60 parts by mass of polyacrylic acid, 30 parts by mass of starch, 15 parts by mass of modified SiO2 particles, 4 parts by mass of benzoyl peroxide, 6 parts by mass of silane coupling agent KH-570 and 4 parts by mass of polyethylene glycol are fed into an internal mixer and stirred evenly, and then the substrate melt is extruded;
[0067] S22, forming a degradable and environmentally friendly plastic film on a cooling roller with the melt in step S21.
[0068] Comparative Example 1
[0069] A method for preparing SiO2 particles is provided, which is different from Example 1 in that the amount of ammonia water added in this comparative example is 3 parts by mass.
[0070] Comparative Example 2
[0071] A method for preparing SiO2 particles is provided, which is different from Example 1 in that the amount of ammonia water added in this comparative example is 12 parts by mass.
[0072] Comparative Example 3
[0073] This comparative example is different from Example 1 in that starch and modified SiO2 particles are not added.
[0074] Specific preparation method:
[0075] S21, 40 parts by mass of polyacrylic acid, 2 parts by mass of benzoyl peroxide, 3 parts by mass of silane coupling agent KH-570 and 2 parts by mass of polyethylene glycol are fed into an internal mixer and stirred evenly, and then the substrate melt is extruded;
[0076] S22, forming a degradable and environmentally friendly plastic film on a cooling roller with the melt in step S21.
[0077] Comparative Example 4
[0078] This comparative example is different from Example 1 in that no modified SiO2 particles are added.
[0079] Specific preparation method:
[0080] S21, 40 parts by mass of polyacrylic acid, 20 parts by mass of starch, 2 parts by mass of benzoyl peroxide, 3 parts by mass of silane coupling agent KH-570 and 2 parts by mass of polyethylene glycol are fed into an internal mixer and stirred evenly, and then the substrate melt is extruded;
[0081] S22, forming a degradable and environmentally friendly plastic film on a cooling roller with the melt in step S21.
[0082] Figure 1 (a)-1(b) are transmission electron microscope photos and scanning electron microscope photos of the modified SiO2 particles prepared in Example 1. It can be seen that the modified SiO2 particles have a cavity structure and an open pore structure. The cavity can carry starch, and the open pore structure allows starch to combine with organic polymers to form a film.
[0083] Figure 2 (a)-2(b) are transmission electron microscope photos of SiO2 particles prepared in Comparative Example 1 and Comparative Example 2, respectively. This shows that excessive or insufficient ammonia content will not form Figure 1 (a) Similar structures.
[0084] Figure 3 is a photo of the degradable and environmentally friendly plastic film prepared in Example 2. Figure 4 The following are photos of the plastic films prepared in Comparative Examples 3 and 4. From the photos, it can be seen that the plastic film prepared without adding starch has the best light transmittance, while the transmittance decreases significantly after adding starch. In Example 2 of the present invention, the light transmittance effect is between the film prepared without adding starch and the film prepared by directly adding starch.
[0085] Figure 5 The transmittance curves of the degradable and environmentally friendly plastic films prepared in Example 3, Comparative Example 3 and Comparative Example 4 are shown. The transmittance spectra can be shown from the experimental results to show that the problem of significantly reduced transmittance caused by directly adding starch can be improved in the present invention.
[0086] Figure 6 This is a scanning electron microscope photo of the degradation of the degradable environmentally friendly plastic film prepared in Example 3. The microstructure shows that the film is dense at first, but after being immersed in water for 90 days, a large number of pores appear in the microstructure of the film, indicating that the film has been degraded, indicating that the plastic film prepared by the present invention is a degradable environmentally friendly plastic film.
[0087] Table 1 Water contact angle results of the degradable environmentally friendly plastic films prepared in the examples and comparative examples
[0088] sample Example 1 Example 2 Example 3 Comparative Example 3 Comparative Example 4 Water contact angle 132.4 125.3 128.5 72.5 86.7
[0089] The water contact angle data in Table 1 show that the coating prepared in the present invention has better hydrophobicity, which can reduce the absorption of water molecules in the environment by starch, thereby increasing the service life of the degradable environmentally friendly plastic film.
[0090] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.
Claims
1. A degradable and environmentally friendly plastic film, characterized in that: The raw materials of plastic film are made of the following materials: Polyacrylic acid: 40-60 parts by mass; Starch: 20-30 parts by weight; Modified SiO2 particles: 10-15 parts by mass; Benzoyl peroxide: 2-4 parts by weight; Silane coupling agent KH-570: 3 to 6 parts by mass; Polyethylene glycol: 2 to 4 parts by weight; The modified SiO2 particles have an incompletely closed cavity structure, the starch is inside the cavity of the modified SiO2 particles, the hydroxyl (-OH) groups on the surface of the modified SiO2 particles in the solution are replaced by alkyl (-CH3) groups, and the diameter of the modified SiO2 particles is 30 to 150 nm.
2. The degradable and environmentally friendly plastic film according to claim 1, characterized in that: The preparation of modified SiO2 particles comprises the following steps: S11, dissolving 0.3 parts by mass of polyacrylic acid in 6-8 parts by mass of ammonia water, stirring for 1 hour, then adding 50-80 parts by mass of anhydrous ethanol, stirring for 2 hours, and finally adding 0.5-1 parts by mass of tetraethyl orthosilicate, continuing to stir and react for 5-10 hours, and finally washing with deionized water to obtain open-pored SiO2 particles; S12. Add 100 parts by mass of anhydrous ethanol to 4 parts by mass of open-pored SiO2 particles, then add 1 to 2 parts by mass of hexamethyldiazapine and stir for 3 to 6 hours, and then centrifuge to obtain modified SiO2 particles.
3. The degradable and environmentally friendly plastic film according to claim 1, characterized in that: The method for preparing the starch inside the cavity of the modified SiO2 particles comprises the following steps: Add 6-9 parts by mass of starch to 50-80 parts by mass of deionized water, heat to dissolve, then add 3-4.5 parts by mass of modified SiO2 particles, stir for 10 minutes, then lower the temperature, let stand to precipitate, immediately centrifuge to obtain white powder, and then wash the white powder with cold water and ethanol.
4. A method for preparing the degradable environmentally friendly plastic film according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: S21, feeding the raw materials described in claim 1 into an internal mixer and stirring them evenly, and then extruding the substrate melt; S22, forming a degradable and environmentally friendly plastic film on a cooling roller with the melt in step S21.
Citation Information
Patent Citations
Crop straw polymer water-absorbing powder
CN104232103A
Preparation method and application of biodegradable plastic thin film
CN107540994A
High-strength biodegradable nano plastic and preparation method thereof
CN109897353A
Modified starch-based biodegradable plastic and preparation method thereof
CN110734633A
Degradable melanin ultraviolet-proof thermal-insulation transparent film and preparation method thereof
CN110982123A